SOME TECHNIQUES TO IMPROVE LISTENING SKILLS - Nina Dwiastuty (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2010)
Listening is much more complex than the thought of human as tape recorders; they took in a bit of information, held it in a sort of medium-term memory, and used it. Listeners are actively payingattention and working on understanding and interpreting what they hear. When listening is considered as a difficult skill, it is all because of the characteristics of the message, the delivery, the listener, and the environment. Teaching listening skills is one of the most difficult tasks for any ESL teacher. This is because successful listening skills are acquired over time and with lots of practice. The key point about techniques is that some of them are teachable. Another point about the techniques is the teacher must be able to exemplify the techniques and show that it is effective. Finally, the techniques need to be repeatable; that is to say, it can be incorporated into the student’s skill for dealing with such problems whenever they arise in the future.Keywords: Listening, teaching, and technique.